Dopamine replacement improves motor learning of an upper extremity task in people with Parkinson disease - Paul, Serene S (Behav Brain Res, 2019)
BACKGROUND: Dopamine replacement medication has positive effects on existing motor skills for people with Parkinson disease (PD), but may have detrimental effects on the learning of motor skills necessary for effective rehabilitation according to the dopamine overdose hypothesis. OBJECTIVES: This study aimed to determine whether dopamine replacement medication (i.e. levodopa) affects: learning of a novel upper extremity task, decrements in skill following withdrawal of practice, the rate of learning, and the transfer of movement skill to untrained upper extremity tasks compared to training “off” medication, in people with PD. METHODS: Participants with mild-moderate PD (Hoehn and Yahr stage 2) were randomized to train “on” (n=12) or “off” (n=11) levodopa medication. Participants practiced 10 blocks of five trials of a functional motor task with their non-dominant upper extremity over three consecutive days (acquisition period), followed by a single block of five trials two and nine days later. Participants were also assessed “on” levodopa with two transfer tasks (the nine-hole peg test and a functional dexterity task) prior to any practice and nine days after the end of the acquisition period. RESULTS: Participants who practiced “on” levodopa medication learned the upper extremity task to a greater extent that those who practiced “off” medication, as determined by retained performance two days after practice. Skill decrement and skill transfer were not significantly different between groups. Rate of learning was unable to be modelled in this sample. CONCLUSIONS: Levodopa medication improved the learning of an upper extremity task in people with mild-moderate PD.